THE INFLUENCE OF BUSINESS RISK, FINANCIAL RISK AND MARKET RISK TOWARDS LQ 45 STOCK PERFORMANCE - Gayuh Raditya Perdana; Sulastri Sulastri; Mohamad Adam; Marlina Widiyanti (UNIB Press, 2019)
The research aims to analyze the influence of Business Risk, Financial Risk and Market Risktowards LQ 45 stock performance. LQ 45 Stock Market period 2012 – 2016 were taken as thesample of this research. This research yields that average DOL value is positive which meansthat the sample studied is an efficient company, with an average DER value of less than100% which means that the company's financial risk level is small and with an average ROErating above 50% means that the company has added value to shareholders.The model usedin this study is multiple regression model. Type of this research is explanatory research. Theresult of the research shows that there is no signifikan impact of the business risk, financialrisk and market risk towards LQ 45. So it can be concluded that the fundamental factor inthis research has no effect on LQ 45 stock performance.